Effects of an early referral system on liver transplantation for hepatoblastoma at Texas Children's Hospital. (27th March 2016) - Kueht, Michael; Thompson, Patrick; Rana, Abbas; Cotton, Ronald; O'Mahony, Christine; Goss, John
Abstract: The purposes of this study were to analyze the effects of an ERS on time to transplantation and to describe our center's experience with OLT for HB. Patients who received OLT for HB between 2000 and 2013 were included. Patient and allograft characteristics, chemotherapy regimens, and prior surgical therapies were examined. The interval between diagnosis and OLT prior to and following the institution of an ERS for transplant was compared. Survival and tumor recurrence were analyzed. Nineteen patients received OLT for HB (mean age 33 months). All children received grafts from deceased donors. Two patients underwent prior resections. Tumor recurred in four patients (21.1%). Both patients who received salvage transplants experienced post‐OLT recurrence. Three of the four recurrences occurred in spite of adjuvant chemotherapy. There were three deaths: two from metastatic disease. One‐ and five‐yr survivals were 86.1% and 73.8%. After the institution of the ERS, the mean interval between tissue diagnosis and OLT was significantly reduced. Our series of 19 patients demonstrates a 21% recurrence of HB following OLT despite chemotherapy. Five‐yr survival reached 73.8%. A system of early referral can effectively reduce times between diagnosis and transplant.